INTERSTATE RELOCATION OF MANUFACTURERS AND BUSINESS CLIMATE. Issue 1 (24th October 2016) - Conroy, Tessa; Deller, Steven; Tsvetkova, Alexandra
Abstract : In this study, we model how traditional factors associated with a supply‐side view of business climate, at times identified with neo‐liberalism, influence interstate relocation patterns of manufacturers using a panel (2000–2011) of the 48 contiguous American states. We find that very few manufacturing firms relocate across state lines in any given year and those that do relocate are relatively small businesses and are most likely to move to neighboring states. Traditional factors associated with business climate, such as taxation, appear to influence manufacturing interstate relocation. Further analysis shows that the tax policy changes necessary for an economically significant effect on relocation are likely infeasible.